Modernist cuisine at home - Myhrvold, Nathan; Bilet, Maxime; Lehuta, Melissa
"This book focuses on cooking equipment, techniques, and recipes."--P. xvii.
Pt. 1. Stocking the modernist kitchen -- pt. 2. The recipes.
Vol. 2 is a spiral bound supplemental "kitchen manual" (220 p.), lacks illustrations and is printed on washable, waterproof paper, both volumes contain indexes.
Issued in slip case.
Keywords: Cooking; Molecular gastronomy